USING SEQUENCED PICTURES ON THE FLICKR SOCIAL NETWORK IN TEACHING WRITING NEWS ITEM FOR THE TENTH GRADE STUDENTS OF SMA 3 PURWOKERTO (ELT Forum: Journal of English Language Teaching, 2013)
This study mainly aims at determining the effectiveness of using Flickr social network in teaching written news item text to improve students’ writing ability and also to find out the significant difference between the students who are taught using Flickr social network and the students who are taught using conventional method (a sequence of pictures). The subject of my research was 64 students of X7 and X8 class of SMA N 3 Purwokerto. The research applied was experimental research. By using purposive sampling, the students of X8 were taken as the samples of the experimental group and the samples of control group were students of X7. In this research, the students were taught using Flickr social network. The result of this research was found by comparing the result of pretest and posttest. I used t-test to find out the significance enhancement. Based on the result of the research, the result of the observed t-value is higher than the critical t-value; observed t-value 3.24 and the critical t-value is 2.04, the result of the writing aspects in the posttest is higher than the pretest, and the percentage of the students who got the score more than 60 in the posttest was 53% while in the pretest was only 16%. Therefore, it can conclude that using Flickr social network can effectively enhance students’ writing ability.